2020
DOI: 10.1136/oemed-2019-106324
|View full text |Cite
|
Sign up to set email alerts
|

Who maintains good health functioning? The contribution of social, work-related and behavioural factors to mental and physical health functioning trajectories in ageing employees

Abstract: ObjectivesThe determinants of poor functioning and subsequent early exit from work are well established but very little is known about the positive determinants of maintaining good functioning among the ageing workforce. We investigated modifiable determinants of maintaining good mental and physical health functioning.MethodsWe used prospective survey data collected across four waves among the midlife employees of the City of Helsinki, Finland, 2000–2017 (n=3342). Health functioning was repeatedly measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Regarding working conditions, a high prevalence of exposure was observed in the group of workers aged 60-64 years for many hazards, in particular for exposure to ergonomic factors, but also to dust, fumes, gases or vapours, excessive noise or vibration, and injury risk, in particular among male manual workers, where the proportion of exposed subjects was above 15%. Higher prevalences of exposure to work hazards among ageing workers have been found in several studies, although the comparability with our results is limited by differences in the age groups examined, as well as how exposure has been measured (Lallukka et al, 2020;Leijten et al, 2015;Robroek et al, 2013). Working during unsocial hours, i.e.…”
Section: Working Conditionssupporting
confidence: 63%
“…Regarding working conditions, a high prevalence of exposure was observed in the group of workers aged 60-64 years for many hazards, in particular for exposure to ergonomic factors, but also to dust, fumes, gases or vapours, excessive noise or vibration, and injury risk, in particular among male manual workers, where the proportion of exposed subjects was above 15%. Higher prevalences of exposure to work hazards among ageing workers have been found in several studies, although the comparability with our results is limited by differences in the age groups examined, as well as how exposure has been measured (Lallukka et al, 2020;Leijten et al, 2015;Robroek et al, 2013). Working during unsocial hours, i.e.…”
Section: Working Conditionssupporting
confidence: 63%
“…Body mass index (BMI) was calculated as weight in kilograms divided by height in meters squared, using self-reports and dichotimized into non-obese (≤ 30 kg/m 2 ) and obese (> 30 kg/m 2 ). Sleep problems were measured by a 4-item version of the Jenkins questionnaire (Jenkins et al 1988 ) and those participants reporting at least one of the four symptoms (trouble falling asleep, wake up several times per night, trouble staying asleep, feeling tired after usual amount of sleep) occurring more than 14 days a month were classified as having sleep problems (Lallukka et al 2020a ). Based on the regular smoking habits the participants were categorized as non-, current, or former smokers.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been found that good sleep supports the maintenance of physical health and functioning, which was replicated in our findings. 26 Our study adds to the literature by identifying factors associated with clinically meaningful physical health and function improvements among women in midlife and by confirming factors associated with general positive aging in midlife and in older individuals.…”
Section: Discussionmentioning
confidence: 99%